The relationship between classical item characteristics and item response time on computer-based testing - Chae, Yoo-mi (Korean J Med Educ, 2019)
PURPOSE: This study investigated the relationship between the item response time (iRT) and classic item analysis indicators obtained from computer-based test (CBT) results and deduce students’ problem-solving behavior using the relationship. METHODS: We retrospectively analyzed the results of the Comprehensive Basic Medical Sciences Examination conducted for 5 years by a CBT system in Dankook University College of Medicine. iRT is defined as the time spent to answer the question. The discrimination index and the difficulty level were used to analyze the items using classical test theory (CTT). The relationship of iRT and the CTT were investigated using a correlation analysis. An analysis of variance was performed to identify the difference between iRT and difficulty level. A regression analysis was conducted to examine the effect of the difficulty index and discrimination index on iRT. RESULTS: iRT increases with increasing difficulty index, and iRT tends to decrease with increasing discrimination index. The students’ effort is increased when they solve difficult items but reduced when they are confronted with items with a high discrimination. The students’ test effort represented by iRT was properly maintained when the items have a ‘desirable’ difficulty and a ‘good’ discrimination. CONCLUSION: The results of our study show that an adequate degree of item difficulty and discrimination is required to increase students’ motivation. It might be inferred that with the combination of CTT and iRT, we can gain insights about the quality of the examination and test behaviors of the students, which can provide us with more powerful tools to improve them.